Physical Mechanisms Controlling the Strength-Deformation Behavior of Frozen Sand: Part 2. - Swan, Christopher W.; Ladd, Charles C.; Germaine, John T.; Anderson, Glen R. (1995)
A high-pressure low-temperature triaxial compression testing system with on-specimen axial strain measurements and lubricated end platens was used to measure the stress-strain-volume change behavior of pluviated Manchester Fine Sand (MFS) from Esilon sub a = 0.001% to 25%. Three types of tests were performed: (1) 99 conventional tests on frozen MFS having four testing variables-relative density, confining pressure, three strain rates, and four temperatures; (2) 10 tests on dense MFS that was frozen after consolidation to effective stresses; and (3) 49 undrained and drained triaxial tests on unfrozen MFS at varying relative density and confining pressure. (MM)